2011
DOI: 10.1029/2011gl047575
|View full text |Cite
|
Sign up to set email alerts
|

Mantle transition zone variations beneath the Ethiopian Rift and Afar: Chemical heterogeneity within a hot mantle?

Abstract: [1] The mantle transition zone (MTZ) structure beneath the Ethiopian Rift and Afar is mapped using receiver functions. The 410 discontinuity is flat and regionally depressed by 30-40 km, most likely due to a hot (≥+250°C) and slow (average dV S > 3 %) upper mantle. The 660 discontinuity is shown to have variations in depth (665-705 km) over short length scales (<200 km). This results in a MTZ with a 'normal' average thickness of 244 km, (i.e., within error of the observed global average). However, local thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 35 publications
5
32
2
Order By: Relevance
“…distances than we observe and are correlated with expected temperature fluctuations. Hetényi et al (2009) andCornwell et al (2011) detected variations in the depth of the '660' at comparable length scales to those observed here using receiver functions.…”
Section: Possible Causes Of Apparent Topography On the '660'mentioning
confidence: 55%
“…distances than we observe and are correlated with expected temperature fluctuations. Hetényi et al (2009) andCornwell et al (2011) detected variations in the depth of the '660' at comparable length scales to those observed here using receiver functions.…”
Section: Possible Causes Of Apparent Topography On the '660'mentioning
confidence: 55%
“…Wright et al (2004) identified the 410 and 660 beneath the Kaapvaal craton slightly deeper than normal. Cornwell et al (2011) found in the Ethiopian Rift and Afar Region local thickness variations of the transition zone between 230 and 260 km. Cornwell et al (2011) found in the Ethiopian Rift and Afar Region local thickness variations of the transition zone between 230 and 260 km.…”
Section: Africamentioning
confidence: 88%
“…In the case of Ethiopia, transition zone thickness, determined by receiver function analysis, shows evidence for thinning compared to the global mean; Cornwell et al (2011) cited this as evidence for high temperatures at transition zone depths, and thus connectivity between shallow low velocities imaged tomographically in Ethiopia (e.g., Bastow et al, 2008;Benoit et al, 2006;Debayle et al, 2001;Hansen et al, 2012;Pasyanos and Nyblade, 2007) and the superplume in the lower mantle beneath.…”
Section: Evidence From Broadband Seismologymentioning
confidence: 99%
“…The consensus emerging from recent studies in Ethiopia is that it is underlain by a broad low velocity anomaly, not a traditional narrow mantle plume (e.g., Bastow et al, 2008;Benoit et al, 2006;Cornwell et al, 2011;Hansen et al, 2012;Ritsema et al, 2010) (Fig. 5).…”
Section: Implications For the Thermochemical State Of The Ethiopian Mmentioning
confidence: 99%